AETIOLOGY, CLINICAL PATTERN AND OUTCOME OF ADULT INTESTINAL OBSTRUCTION IN JOS, NORTH CENTRAL NIGERIA - Ojo, E.O (Afr J Med Med Sci, 2014)
BACKGROUND: Intestinal obstruction is a challenging surgical emergency with major clinical and financial burden as well as considerable morbidity and mortality around the world. This study was conducted to determine the aetiological spectrums, clinical course and outcome of intestinal obstruction in North Central, Nigeria METHODS: A prospective cross sectional study of all consecutive patients presenting with intestinal obstruction to Jos University Teaching Hospital, Jos, Nigeria between June 2010 and May 2013. RESULTS: A total of 217 patients constituting about 10.1% of 2,149 non-trauma surgical emergencies were treated, with male to female ratio of 1.15:1. Their age ranged from 17–98 years (mean 42.5±15.5 years) with a peak age group of 21–40 years. Adhesions 112 (51.6%) with peak incidence in the fourth decade was the leading cause of obstructions followed by neoplasms 39 (18%), hernia 28 (12.9%) and volvulus 22 (10.17%). Majority of obstructions involved the small bowel 169 (77.8%) and strangulated bowel was present in 56 (25.8%) patients. Surgical intervention was carried out in 169 (77.9%) and the rest were treated conservatively. Morbidity consisting mainly of local wound, peritoneal sepsis and systemic complications occurred in 63 (29 %) patients. The overall mortality rate was 12 (5.5%) and this was predicted by the presence of strangulations, shock, loop obstructions and delayed presentation. The mean inpatient admission in days was 14.4±11.9 days (range 1–75 days). CONCLUSION: Bowel obstruction constitutes about 10% of all non-trauma surgical emergencies. Adhesions, neoplasm, hernia and volvulus were the leading causes. Morbidity and mortality remains high due to intestinal strangulation. Concerted efforts directed towards adhesion prevention, early elective hernia repair, prompt screening and cancers treatment will therefore likely reduce the morbidity and mortality of bowel obstruction.